In Situ Conversion of Metal-Organic Frameworks into VO2-V3S4 Heterocatalyst Embedded Layered Porous Carbon as an "All-in-One" Host for Lithium-Sulfur Batteries - Seo, Seung-Deok; Yu, Seungho; Park, Sangbaek; Kim, Dong-Wan (WILEY-V C H VERLAG GMBH, 2020)
Although lithium-sulfur batteries exhibit a fivefold higher energy density than commercial lithium-ion batteries, their volume expansion and insulating nature, and intrinsic polysulfide shuttle have hindered their practical application. An alternative sulfur host is necessary to realize porous, conductive, and polar functions; however, there is a tradeoff among these three critical factors in material design. Here, the authors report a layered porous carbon (LPC) with VO2/V3S4 heterostructures using one-step carbonization-sulfidation of metal-organic framework templates as a sulfur host that meets all the criteria. In situ conversion of V-O ions into V3S4 nuclei in the confined 2D space generated by dynamic formation of the LPC matrix creates {200}-facet-exposed V3S4 nanosheets decorated with tiny VO2 nanoparticles. The VO2/V3S4 @ LPC composite facilitates high sulfur loading (70 wt%), superior energy density (1022 mA h g(-1) at 0.2 C, 100 cycles), and long-term cyclability (665 mA h g(-1) at 1 C, 1000 cycles). The enhanced Li-S chemistry is attributed to the synergistic heterocatalytic behavior of polar VO2 and conductive V3S4 in the soft porous LPC scaffold, which accelerates polysulfide adsorption, conversion, and charge-transfer ability simultaneously.
Keywords: CATALYTIC-OXIDATION; POLYSULFIDES; CATHODE; HETEROSTRUCTURES; GRAPHENE; SURFACE; ADSORPTION; PYROLYSIS; STABILITY; DIFFUSION